2014
DOI: 10.1007/s10661-014-3995-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi-temporal landsat satellite images for monitoring land surface temperature of municipal solid waste disposal sites

Abstract: This studypresents a remote sensing application of using time series Landsat satellite images for monitoring the Trail Road and Nepean municipal solid waste (MSW) disposal sites in Ottawa, Ontario, Canada. Currently, the Trail Road landfill is in operation; however, during the 1960s and 1980s, the city relied heavily on the Nepean landfill. More than 400 Landsat satellite images were acquired from the US Geological Survey (USGS) data archive between 1984 and 2011. Atmospheric correction was conducted on the La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…In this research work, the authors aim to utilize remote sensing and GIS techniques to assess the relationship between the built-up area and the reported real GDP in seven major cities in Canada. Instead of using the night-time light images, we employed the multi-temporal Landsat TM satellite images, which are free to the public and have a short revisit time [16]. As the real GDP of Canada is mainly made up of mining and manufacturing services, thus we place an emphasis on the built-up land with industrial use and compare the remote sensing-derived built-up index with respect to the corresponding real GDP of these seven major cities from 2005 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In this research work, the authors aim to utilize remote sensing and GIS techniques to assess the relationship between the built-up area and the reported real GDP in seven major cities in Canada. Instead of using the night-time light images, we employed the multi-temporal Landsat TM satellite images, which are free to the public and have a short revisit time [16]. As the real GDP of Canada is mainly made up of mining and manufacturing services, thus we place an emphasis on the built-up land with industrial use and compare the remote sensing-derived built-up index with respect to the corresponding real GDP of these seven major cities from 2005 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2014) Através dos dados obtidos verificou-se que a estimativa da temperatura da superfície oriunda do sensoriamento remoto é de extrema importância para estudos em aterros e lixões, conforme discutido por outros autores (Yang et al, 2008;Silvestri & Omri, 2008;Choudhury & Das, 2012;Ohri et al, 2015). Contudo, considera-se relevante a complementação com dados de campo visto que a temperatura do solo e abaixo deste pode apresentar variações, de acordo com os estudos de Yesiller & Hanson (2003), Hanson, Yesiller & Swarbrick (2005), Mariano e Moura (2009) e Rowe (1998).…”
Section: Discussionunclassified
“…Platforms such as unmanned aerial vehicles (UAVs) or drones, airborne or space borne flying objects like airplanes or satellites can be used with limited spatial resolution properties. Yan et al (2014) showed that LANDSAT images are informative on the lateral delineation of landfills by observing the land surface temperature. Dumps usually have an increased temperature comparatively to the surrounding areas.…”
Section: Identifying Waste In Forgotten Dumpsites and Waste Charactermentioning
confidence: 99%